Schinus molle L.: Perfil químico e biológico de óleos essenciais e extrato aquoso - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Schinus molle L. (Anacardiaceae) is a medicinal tree native from South of Brazil and traditionally known as aroeira, aroeira-da-praia and aroeira-salsa. In the traditional medicine, is used as analgesic, antifungic, antihypertensive, anti-inflammatory, antimicrobial, antisseptic, diuretic and insecticide. Considering, the wide utilization of the medicinal specie in the traditional medicine, the therapeutic potential and the chemical variability in the different seasons of the year, the work aimed to determine the phytochemical profile of the essential oil of S. molle leaves in four seasons of the year and to evaluate the biological activities and investigating the genotoxicity and cardioprotective effects of the aqueous extracts. The essential oils were characterized by gas chromatography-mass spectrometry (GC-MS) and high-performance thin layer chromatography (HPLC). The antioxidant activity was determined by phosphomolybdenum assay, DPPH and TBARS. For the essential oil (summer), the antimicrobial activity was evaluated against Proteus mirabilis, Candida albicans, Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa by minimal inhibitory concentration (MIC). The cytotoxic activity was verified by cell viability of tumor cell and normal kidney cell lines. The anti-inflammatory action of the essential oil was evaluated by mechanical sensitivity test (Von Frey), to cold and paw edema. The fraction soluble in ethanol of S. molle (FSESM) was submitted to acute toxicity studies, genotoxicity and cardioprotective effect in animals. The chemical profile for the essential oils evidenced to summer - the caryophyllene oxide (8,88%), β-pinene (8,84%), E–caryophyllene (7,53%), limonene (6,11%), α-muurolene (5,42%) and spatulenol (5,88%); spring – limonene (5,27%); fall – zonarene (9,27%), globulol (7,84%) and camphene (5,19%); winter – muurolol (19,40%), α-cadinol (16,32%), ledol (14,46%) and caryophyllene oxide (11,44%). The HPLC identified the chemical variability of essential oils in the four seasons. The antimicrobial activity showed in 0,203 g/mL (MIC) against E. coli. The cytotoxicity was verified to three lineages of tumoral cells: BT-549 (breast cancer), SK- MEL (melanoma) and KB (keratin-forming tumor cells) for IC50 (mean inhibitory concentration) for values of 70 μg/mL, 92 μg/mL and 100 μg/mL, respectively. And to the normal kidney cells (VERO cells), the cytotoxicity in IC50 79 μg/mL was verified. The anti-inflammatory activity was considered significant. In addition, the antioxidant activity was proved it. The FSESM chemical profile revealed organic acids, derived from benzoic acid, derivates of phenylpropanoid acid, flavonoids, procyanidins, o- glycosylated megastigmanes and fatty acids. FSESM did not demonstrate toxic effects at maximum dose of 2000 mg/kg. In the genotoxicity assay, FSESM (5, 50 and 300 mg/kg) did not caused damages in the DNA and erythrocytes. The cardioprotective effects of FSESM were not proven by evaluation of diuretic activity and vascular reactivity in mesenteric beds. For this research, was identified a chemical variability of the composition, the antimicrobial, cytotoxic and antioxidant activity of the oil essential from leaves of S. molle, in addition to prove the absence of genotoxicity and the safety oral administration of FSESM.
Keywords: Anacardiaceae.; Aroeira; Antioxidante; Genotoxicidade; Óleo volátil; Anacardiaceae; Aroeira; Antioxidant; Genotoxicity; Volatile oil; Ciências da Saúde